Linking bacterial and fungal assemblages to soil nutrient cycling within different aggregate sizes in agroecosystem - Zhang, Shan; Hu, Wanjin; Xu, Yue; Zhong, Hui; Kong, Zhaoyu; Wu, Lan (Frontiers in Microbiology, 2022)
Soil aggregates provide spatially heterogeneous microhabitats that support the coexistence of soil microbes. However, there remains a lack of detailed assessment of the mechanism underlying aggregate-microbiome formation and impact on soil function. Here, the microbial assemblages within four different aggregate sizes and their correlation with microbial activities related to nutrient cycling were studied in rice fields in Southern China. The results show that deterministic and stochastic processes govern bacterial and fungal assemblages in agricultural soil, respectively. The contribution of determinism to bacterial assemblage improved as aggregate size decreased. In contrast, the importance of stochasticity to fungal assemblage was higher in macroaggregates (>0.25 mm in diameter) than in microaggregates (<0.25 mm). The association between microbial assemblages and nutrient cycling was aggregate-specific. Compared with microaggregates, the impacts of bacterial and fungal assemblages on carbon, nitrogen, and phosphorus cycling within macroaggregates were more easily regulated by soil properties (i.e., soil organic carbon and total phosphorus). Additionally, soil nutrient cycling was positively correlated with deterministic bacterial assemblage but negatively correlated with stochastic fungal assemblage in microaggregates, implying that bacterial community may accelerate soil functions when deterministic selection increases. Overall, our study illustrates the ecological mechanisms underlying the association between microbial assemblages and soil functions in aggregates and highlights that the assembly of aggregate microbes should be explicitly considered for revealing the ecological interactions between agricultural soil and microbial communities.